1992
DOI: 10.1111/j.1365-2044.1992.tb03206.x
|View full text |Cite
|
Sign up to set email alerts
|

Baroreflex control of heart rate during high thoracic epidural anaesthesia

Abstract: SummaryBaroreflex control of heart rate after cardiac sympathectomy induced by thoracic epidural anaesthesia was evaluated in 30 patients who were randomly assigned to group I (bupivacaine 0.25%). group 2 (bupivacaine 0.5%) or group 3 (control). Plasma volume expanders were given to equalise preload conditions. as assessed using transoesophageal echocardiography. All measurements were made under general anaesthesia. Barorejex sensitivity was determined from the heart rate response to phenylephrine and nitrogly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0
4

Year Published

1995
1995
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 21 publications
1
8
0
4
Order By: Relevance
“…However, Goertz et al [11] reported that epidural anesthesia producing analgesia above T1 reduced baroreflex sensitivity, as calculated with the depressor test. The major differences between the two studies were that, in the study of Takeshima and Dohi [10], CTEA was performed with lidocaine, with the patient conscious, whereas, in the study of Goertz et al [11], CTEA was induced with bupivacaine during nitrous oxide-fentanyl anesthesia.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…However, Goertz et al [11] reported that epidural anesthesia producing analgesia above T1 reduced baroreflex sensitivity, as calculated with the depressor test. The major differences between the two studies were that, in the study of Takeshima and Dohi [10], CTEA was performed with lidocaine, with the patient conscious, whereas, in the study of Goertz et al [11], CTEA was induced with bupivacaine during nitrous oxide-fentanyl anesthesia.…”
Section: Discussionmentioning
confidence: 98%
“…However, Goertz et al [11] reported that epidural anesthesia producing analgesia above T1 reduced baroreflex sensitivity, as calculated with the depressor test. The major differences between the two studies were that, in the study of Takeshima and Dohi [10], CTEA was performed with lidocaine, with the patient conscious, whereas, in the study of Goertz et al [11], CTEA was induced with bupivacaine during nitrous oxide-fentanyl anesthesia. Our present findings are in contrast to those of Takeshima and Dohi [10], but are quite similar to those of Goertz et al [11], although the scope of our study probably encompassed factors other than the depressor response.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Baroreflex sensitivity has been reported to be suppressed by volatile anesthetics (10), cervicothoracic epidural anesthesia (11), and large doses of IV local anesthetics (12). Therefore, baroreflexes are significantly affected by combined general/epidural anesthesia with cardiac sympathectomy (13,14). Sudden bradycardia and severe hypotension secondary to decreased venous return or surgical bleeding can occur during combined general/thoracic epidural anesthesia because of decreased sympathetic response and increased vagal activation.…”
mentioning
confidence: 97%